The scandal of the century and other writings - Márquez, Gabriel García (Alfred A Knopf, 2019)
"From one of the titans of twentieth-century literature, collected here for the first time: a selection of his journalism from the late 1940s to the mid-1980s--work that he considered even more important to his legacy than his universally acclaimed works of fiction"--